A comprehensive review on different approaches for CO2 utilization and conversion pathways. (8th June 2021) - Saravanan, A.; Senthil kumar, P.; Vo, Dai-Viet N.; Jeevanantham, S.; Bhuvaneswari, V.; Anantha Narayanan, V.; Yaashikaa, P.R.; Swetha, S.; Reshma, B.
Graphical abstract: Highlights: CO2 was used as an inexpensive feedstock for various fuels and chemicals production. Explained various utilization approaches and their mechanisms for CO2 mitigation. Discussed the various CO2 conversion processes. Current status and Scope for further research on CO2 conversion has been discussed. Abstract: Carbon dioxide (CO2 ) is a odourless and colourless gas which plays a noteworthy role in the climate and weather changes. Different natural and anthropogenic activities induces CO2 emission in the environment. Though CO2 causes global warming, it acts as an essential element for photosynthesis process in plants. CO2 can also be used as an inexpensive feedstock for the production of various fuels and chemicals. Many approaches like electrochemical, thermal, biochemical, chemo-enzymatic and photocatalytic methods are available by means of which the harmful CO2 is captured from the environment. Similarly, via different chemical, physical and biological processes, it can be converted into useful products like fuels and chemicals. This review mainly focuses on various utilization approaches and their mechanisms for CO2 mitigation. In addition, CO2 conversion processes like hydrogenation, esterification, methanation, reforming, and reverse water-gas shift (RWGS) reactions, their mechanisms and their current status along with future perspectives were comprehensively discussed.